Nilai Pendidikan Dalam Novel Ngeri-Ngeri Sedap Karya Bene Rajagukguk: Pendekatan Sosiologi Sastra - Nainggolan, Elisabet Natalia Hilleri; Harahap, Nurhayati; Lubis, Haris Sutan (Peneliti.net, 2024)
Literary works are born because of the power of imagination in which there are ideas, thoughts and feelings of an author. This power of imagination is what is able to distinguish one literary work from another. One form of literary work that is much in demand among the public is the novel. Novels as a form of literary work are expected to produce positive values for readers, so that they can be sensitive to problems related to social life and encourage good behavior. The novel Ngeri-Ngeri Sedap by Bene Rajagukguk is a literary work that can be studied using a literary sociology approach. The values contained in literary works can be educational values such as social values, moral values, cultural values and religious values. The aim of this research is to reveal the form of educational values contained in the novel Ngeri-Ngeri Sedap by Bene Rajagukguk. This study used descriptive qualitative method. The data collection technique begins with reading the novel Ngeri-Ngeri Sedap. Furthermore, the data analysis techniques in this research start from data reduction, data codification, data classification, data description, data interpretation, and data verification. The Literary Sociology approach used is from Sapardi Djoko Damono, namely the classification of Educational Values. The results of this research produce four forms of educational value according to Sukardi, namely social values, moral values, cultural values and religious values.